BUSINESS TOURISM AS SOCIOECONOMIC INSTRUMENT OF REGIONAL INNOVATIVE DEVELOPMENT - Natalya N. Morozova (Advanced Engineering Research, 2012)
The current state of the business meeting industry, the rate of delivery and performance features of MICE industry at the national and regional levels are analyzed. It is concluded that amid the growing globalization, business tourism acts as an innovation development source and as a catalyst for the socioeconomic development of the regional economy in the modern business community infrastructure.